Highly sensitive and flexible capacitive elastomeric sensors for compressive strain measurements. (March 2021) - Qiu, Aidong; Jia, Qingxiu; Yu, Huimin; Oh, Jeong-A; Li, Danda; Hsu, Hung-Yao; Kawashima, Nobuyuki; Zhuge, Yan; Ma, Jun
Abstract: Flexible capacitive strain sensors are known for low hysteresis and high linearity; but their application to accurate measurements of compressive strains remains a challenge. In this study, we developed an elastomeric nanocomposite dielectric for flexible capacitive strain sensors to achieve high sensitivity under static compression. A solid-state raw elastomer (EPDM) was used to replace the popular liquid-state silicon rubber as the matrix for these sensors, since the two-roll milling process proved effective in uniformly dispersing the electro-conductive carbon black nanoparticles in EPDM. The sensitivity was tuned by controlling the nanoparticle fractions in the dielectric. At 3 wt.% of nanoparticles, the capacitive nanocomposite sensor displayed sensitivity of over 3.5, capable of measuring compressive strains up to 30 %. Featuring high linearity of over 99.4 %, good cyclic stability and low cyclic hysteresis, these sensors accurately measured compressive strains under static loading.